A BSSS Algorithm for the Location Problem with Minimum Square Error. (2nd December 2009) - Fathali, Jafar; Zaferanieh, Mehdi; Nezakati, Ahmad
Abstract : Letn weighted points be given in the planeR 2 . For each point a radius is given which is the expected ideal distance from this point to a new facility. We want to find the location of a new facility such that the sum of the weighted errors between the existing points and this new facility is minimized. This is in fact a nonconvex optimization problem. We show that the optimal solution lies in an extended rectangular hull of the existing points. Based on this finding then an efficient big square small square (BSSS) procedure is proposed.